2004
DOI: 10.1088/0953-2048/17/11/011
|View full text |Cite
|
Sign up to set email alerts
|

Spray pyrolysis for highTcsuperconductors films

Abstract: Spray pyrolysis at high temperature is reviewed and applied to the formation of epitaxial thick layers of YBa 2 Cu 3 O 7 (YBCO). The necessary conditions to enhance the texture quality and the critical current density are discussed. High critical current densities, over 1.0 MA cm −2 (at 77 K, self-field), are reported, making this technique very promising for low cost applications. This emphasizes the need for more comprehensive studies regarding the chemical phenomena involved in film deposition by spray pyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…As reported by Odier et al, 17 M. Langlet et al, 23 spray pyrolysis deposition is generally divided into three principal modes depending upon the temperature range of the pyrolysis: (1) at a low temperature, the spray droplets reach the substrate as a solution and liquid films possibly form. If the solvent evaporates from the droplets and if hydrolysis takes place, then gel films can grow in the so-called 'pyrosol-gel' process; (2) if the particles receive a sufficiently large amount of heat during their routes, the solvent evaporates and dry particles precipitate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As reported by Odier et al, 17 M. Langlet et al, 23 spray pyrolysis deposition is generally divided into three principal modes depending upon the temperature range of the pyrolysis: (1) at a low temperature, the spray droplets reach the substrate as a solution and liquid films possibly form. If the solvent evaporates from the droplets and if hydrolysis takes place, then gel films can grow in the so-called 'pyrosol-gel' process; (2) if the particles receive a sufficiently large amount of heat during their routes, the solvent evaporates and dry particles precipitate.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the high temperature spray pyrolysis technique could be classified among the numerous chemical vapour deposition methods. However, an alternative 17 would be that CuO is deposited on a hot substrate from a nitrate solution and a powdered film is obtained, due to a decomposition of the nitrate into CuO small particles in the mist. The film is formed by small solid particles that aggregate to form a film.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Precursor mists are decomposed thermally as chemical vapor and deposited as films on the substrate surface. Several groups have studied on this spray pyrolysis method for the fabrication of YBCO films at atmospheric pressure [6][7][8][9]. Vergniéres et al [9] reported that good quality YBCO films were deposited on metallic substrate as well as on single crystal substrate but the J c of the films still much lower than 1 MA/cm 2 .…”
Section: Introductionmentioning
confidence: 99%